JoJo loves BowBow - Siwa, JoJo (London Puffin, 2018)
Named for JoJo's iconic fashion bows, BowBow Siwa is a superstar in her own right, with more than one million Instagram followers! BowBow has her own stuffed animal likeness, and she and her dog-mom, JoJo, are dedicated to sparkles, bows, and everything cute. This photographic, full-color gift book will feature never-before-seen shots of BowBow and JoJo, giving fans an exclusive insiders' peek into the dazzling duo's daily lives. A perfect gift item, JoJo Loves BowBow will charm Siwanatorz and followers of Instagram-famous pups alike
Photography
2
Keywords: Dogs -- Pictorial works -- Juvenile literature; Photography of dogs